Renal Volume in ADPKD Patient Evaluation - M. Galliani; E. Vitaliano; S. Chicca; L. Calvaruso; L. Di Lullo; F. Iorio; M. E. Tosti; A. Paone (International Journal of Nephrology)
The clinical manifestations of ADPKD are related to the growth of renal cysts. Renal volume has been recognised as the biomarker that is able to identify those patients at risk of complications (hypertension and haematuria) and at risk of progression to End Stage Renal Disease (ESRD). Recently, several scores have been introduced to predict the evolution of ADPKD. The Mayo Clinic Group developed a classification based on renal volume as measured by CT or MRI and corrected for age and height (Ht-TKV); this allowed predicting the evolution of the disease, but it has not been fully validated so far. In addition, it is used to identify patients labelled as “fast progressors” and eligible for Tolvaptan therapy according to the European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) recommendations. We studied 80 patients who underwent MRI and had been classified as ADPKD typical form (class 1A-1E). A significant correlation between renal volume, hypertension, and low GFR was found (p<0.005). A progressive increase in disease severity has been found across the different Mayo classes; 41.2% were eligible for Tolvaptan therapy. The results demonstrate that the Mayo method is easy to perform and provides valid information in order to identify with rapidly progressing disease.